The Power of Gamification: How Kahoot! Transforms Motivation and Learning in Primary Science Education - Desembra Sohilait; Paul Arjanto; Seng Tong Chong; Maria Imaculada da Conceição Soares (Faculty of Education Universitas Negeri Malang, 2025)
This study investigates the impact of Kahoot! on elementary students' motivation and learning outcomes in science education. Using a quantitative experimental one-group pre-test post-test design, 24 sixth-grade students participated, with data collected through a structured motivation questionnaire and a science comprehension test. Statistical analysis, including the Wilcoxon Signed-Rank Test, revealed a significant increase in motivation, with mean scores rising from 62.125 (Pre-Test) to 83.25 (Post-Test) and a p-value of .000 confirming the intervention's effectiveness. The findings align with self-determination theory, emphasizing autonomy, competence, and relatedness in fostering motivation. This study highlights the potential of game-based learning to enhance student engagement and suggests integrating digital platforms like Kahoot! into curricula to maximize learning outcomes. Future research should explore long-term effects and broader applications of gamification in primary education.